2017
DOI: 10.1016/j.idcr.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Atypical hemolytic uremic syndrome triggered by varicella infection

Abstract: Varicella Zoster Virus (VZV) is a well-known virus that belongs to the Herpesviridae family which induces a self-limited disease except in specific cases in particular among stem cell transplant patients. This virus is not known however to trigger atypical Hemolytic Uremic Syndrome (aHUS). Here we report the case of a six-year-old boy who was hospitalized with fever and abdominal pains associated to pruritic and vesicular rash, thrombocytopenia and acute renal failure. He was diagnosed with aHUS precipitated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Genetic or acquired dysregulation of the alternative complement pathway is highly implicated in the pathogenesis of aHUS [ 3 , 6 ]. In genetically susceptible individuals, many triggers have been linked to the development of aHUS, including pregnancy; transplantation; vaccination; and viral infections such as cytomegalovirus, Epstein–Barr virus, influenza, varicella, and Hepatitis B [ 4 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic or acquired dysregulation of the alternative complement pathway is highly implicated in the pathogenesis of aHUS [ 3 , 6 ]. In genetically susceptible individuals, many triggers have been linked to the development of aHUS, including pregnancy; transplantation; vaccination; and viral infections such as cytomegalovirus, Epstein–Barr virus, influenza, varicella, and Hepatitis B [ 4 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…HUS is mainly a disease of children, with more than 90% of the cases typically occurring secondary to infection with Shiga-like toxin producing Escherichia coli (O157:H7 serotype) or other bacteria, such as Streptococcus pneumoniae and Shigella [ 1 , 2 ]. Atypical hemolytic uremic syndrome (aHUS) accounts for 5–10% of HUS cases, and it is named so because it is not caused by the typical HUS triggers [ 3 , 4 , 5 ]. Genetic or acquired dysregulation of the alternative complement proteins, particularly factors H, I, and B; membrane cofactor protein; and complement 3, is implicated in the pathogenesis of aHUS in 40–60% of the cases [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VZV infection involves the same complex of fusion proteins as other herpesviruses; however, it is more oriented toward cell-to-cell fusion than virus-to-cell fusion [ 153 ]. As for HSV, few cases have described the occurrence of nephropathy triggered by VZV infection; they mainly presented as glomerulonephritis [ 154 , 155 , 156 , 157 ], but also possibly as nephrotic syndrome [ 158 , 159 ] or thrombotic microangiopathy [ 160 ]. It should be noted that none of these studies demonstrated viral antigens in renal biopsies.…”
Section: The Herpesviridae Familymentioning
confidence: 99%